Ciało i jego sens - MIKULSKA, Patrycja (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2015)
The author discusses two books related to John Paul II’s theology of the body: Corpo e trascendenza. L’antropologia fi losofi ca nella teologia del corpo di Giovanni Paolo II [“Body and Transcendence. Philosophical Anthropology in the Theology of the Body of John Paul II”] by Jarosław Merecki, SDS, and Teologiczna semantyka ciała [“Theological Semantics of Sex”] by Jarosław Kupczak, OP. The former presents the philosophical presuppositions of the theological theory of the human body, while the latter focuses on the problems related to the use of sexual metaphors in theology. The author also formulates critical remarks concerning both monographs, pointing to the insuffi cient treat-ment of the fundamental concept of experience, and especially of the question of the relationship between philosophy and theology, with their underlying theories of experience, and the particular instances of experience of individuals.